An unusual cause of gynaecomastia. (20th July 2011) - Subbiah, Sridhar; Walia, Rama; Kumar, Santhosh; Nahar, Uma; Bhansali, Anil
Abstract : Gynaecomastia in adolescents and young adults is a common endocrine disorder with usually benign aetiology. However, gynaecomastia in middle-aged men is uncommon and warrants intensive search to unravel its aetiology. The authors report a 42-year-old male who presented with gynaecomastia due to feminising adrenocortical carcinoma.